Peptidic Probes to Capture Enzyme Activity Using Novel Solid Phase Compatible Warheads - McGouran, Joanna (My University, 2026)
Activity-Based Probes (ABPs) are invaluable tools for investigating enzymatic activity but can suffer from onerous syntheses and low stability in complex proteomes. Herein, we present the first synthesis of a robust, vinyl methyl ester (VME), bearing amino acid, which is compatible with solid phase peptide synthesis (SPPS). Novel peptidic probes incorporating the VME motif were prepared, and their labeling activity was investigated against the deubiquitinating enzyme (DUB) Otubain 1 (OTUB1), a critical cysteine protease DUB with remarkable specificity for Lys48 linked polyubiquitin chains. OTUB1 is implicated in DNA repair and immune response mechanisms and is currently considered a biomarker for tumorigenesis. A probe featuring the VME warhead demonstrated high reactivity and selectivity toward OTUB1, highlighting the significant potential of this approach to create robust and selective covalent tools for interrogating cysteine isopeptidases.
PUBLISHED